Assessment of the Development Role of a Statutory Body from a Customer Perspective: A Relationship Marketing Approach - Oei , Fuk Jin; Ogunlana, Stephen O. (Penerbit Universiti Sains Malaysia, 2006)
The importance of the relationship between an institution and its constituents is examined through establishing a model of exchange relationship’s three key important constructs (satisfaction, trust and commitment), which is adopted from the Customer Relationship Marketing/Management (CRM) concept. These three key constructs have been viewed as essential ingredients for successful long-term relationship in private sector CRM. The model is tested using data from the Building and Construction Authority (BCA) of Singapore. It is then compared with a rival model that does not have satisfaction, trust and commitment as mediating variables. The result shows that the model with the three key constructs as mediating variables is better. Understanding the impact of the mediating variables on outcome behaviours can lead to more participation and survival of the institution. Proposals for further research and the research limitation are given at the end of the paper.